Rational design of novel benzisoxazole derivatives with acetylcholinesterase inhibitory and serotoninergic 5-HT(4) receptors activities for the treatment of Alzheimer’s disease - Lalut, Julien (Sci Rep, 2020)
A rigidification strategy was applied to the preclinical candidate donecopride, an acetylcholinesterase inhibitor possessing 5-HT(4)R agonist activity. Inspired by promising bioactive benzisoxazole compounds, we have conducted a pharmacomodulation study to generate a novel series of multitarget directed ligands. The chemical synthesis of the ligand was optimized and compounds were evaluated in vitro against each target and in cellulo. Structure-activity relationship was supported by docking analysis in human acetylcholinesterase binding site. Among the synthesized compounds, we have identified a novel hybrid 32a (3-[2-[1-(cyclohexylmethyl)-4-piperidyl]ethyl]-4-methoxy-1,2-benzoxazole) able to display nanomolar acetylcholinesterase inhibitory effects and nanomolar Ki for 5-HT(4)R.